Effect of Changing Trends in Services Marketing on the Performance of a Glaucoma Clinic: A Retrospective Study. (September 2017) - Mukherjee, Bhaskar; Majumdar, Malini
A 5 years' retrospective study was conducted at a Kolkata-based trust eye hospital. Records were derived from the hospital information system (HIS). From 2010 to 2015, all the other Ps of services marketing were constant except product (P1), price (P3) and promotion (P4). A paradigm shift in P1 was observed with the introduction of higher generation imported glaucoma investigation machines. Price (P3) changes of glaucoma services were observed. State-of-the-art, high-priced, top-of-the-order foreign optical coherence tomography (OCT) machine and neodymium-doped yttrium aluminium garnet (Nd:YAG) laser machine were promoted (P4) along with regular promotion of glaucoma awareness among OPD patients through effective health communication and patient education, leading to increase of glaucoma clinic consultation financial performance from 27.8 per cent in 2011–2012 to 73.9 per cent in 2014–2015 along with other statistics. The reasons for the sudden decrease in performance in 2013–2014 was analyzed.